Hierarchy and Typology of Political Culture - Raihani Dewi Nasution; Fasrah Indah; Raden Bagus Astaman; Ahmad Winaldi; Elly Warnisyah Harahap (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This article discusses political structure and culture with a focus on several key dimensions, namely the physical structure of politics, the social structure of politics, and various types of political culture. The physical structure of politics refers to the formal institutions and political mechanisms that influence the process of political action. The socio-political structure includes the distribution of power and social hierarchies that influence political dynamics in society. Furthermore, this article outlines the different types of political culture, including a political parochial culture that shows minimal involvement in national political affairs, a political subjective culture that reflects individuals' political attitudes and orientations towards power and political participation, and a political participatory culture that encourage active participation in the political process. Through an analysis of the physical and socio-political structures, as well as various political cultures, this article provides a more accurate understanding of the complexity of politics in modern societies. The implications of this understanding for public policy development and political system development are also discussed in depth.